Systematic review with meta‐analysis: portal vein recanalisation and transjugular intrahepatic portosystemic shunt for portal vein thrombosis. Issue 1 (18th November 2018) - Rodrigues, Susana G.; Sixt, Sebastian; Abraldes, Juan G.; De Gottardi, Andrea; Klinger, Christoph; Bosch, Jaime; Baumgartner, Iris; Berzigotti, Annalisa
Summary: Background: Transjugular intrahepatic portosystemic shunt has been increasingly used in patients with portal vein thrombosis to obtain patency, but evidenced‐based decisions are challenging. Aim: To evaluate published data on efficacy and safety of endovascular therapy in portal vein thrombosis. Methods: Systematic search of PubMed, ISI, Scopus, and Embase for studies (in English, until October 2017) reporting feasibility, safety, 12‐month portal vein recanalisation, transjugular intrahepatic portosystemic shunt patency, and survival in patients with benign portal vein thrombosis undergoing endovascular treatment. An independent extraction of articles using predefined data fields and quality indicators was used; pooled analyses based on random‐effects models; heterogeneity assessment by Cochran's Q, I 2 statistic, subgroup analyses, and meta‐regression. Results: Thirteen studies including 399 patients (92% cirrhosis; portal vein thrombosis: complete 46%, chronic 87%, cavernous transformation 17%, superior mesenteric vein involvement 55%) were included. Transjugular intrahepatic portosystemic shunt was technically feasible in 95% (95% CI: 89%‐98%) with heterogeneity ( I 2 = 57%, P < 0.001) explained by cavernous transformation. Major complications occurred in 10% (95% CI: 6.0%‐18.0%; I 2 = 52%, P = 0.55). Additional catheter‐directed thrombolysis was associated with more complications compared to transjugular intrahepatic portosystemic shunt alone or plus thrombectomy (17.6% vs 3.3%). Twelve‐month portal vein recanalisation was 79% (95% CI: 67%‐88%; I 2 = 78%, P < 0.01). Shunt patency at 12 months was 84% (95% CI: 76%‐90%; I 2 = 62%, P < 0.01). Overall 12‐month survival rate was 89%, with no heterogeneity. Conclusions: Transjugular intrahepatic portosystemic shunt for portal vein thrombosis recanalisation was highly feasible, effective, and safe. Cavernous transformation was the main determinant of technical failure. Additional catheter‐directed thrombolysis was associated with higher risk of severe complications.